Differential changes in gene expression in human brain during late first trimester and early second trimester of pregnancy. (5th February 2014) - Iruretagoyena, J. I.; Davis, W.; Bird, C.; Olsen, J.; Radue, R.; Teo Broman, A.; Kendziorski, C.; BonDurant, S. Splinter; Golos, T.; Bird, I.; Shah, D.
ABSTRACT Objective This study aimed to describe brain development during the first (B1) and second trimester (B3) in human fetuses. Design Ten brains from 10 to 18 weeks of gestational age (GA) were collected, and the RNA was used for transcriptome analysis (Affymetrix 1.0 ST microarray chip). Differences in brain development within 10 to 18 GA were investigated by dividing the sample into 10 to 12 (B1), 13 to 15(B2) and 16 to 18(B3) weeks. A fold change of 2 or above, with a false discovery rate of 5%, was used as cut‐off to determine differential gene expression for individual genes. Quantitative real‐time PCR was used to confirm differences. Tests for enrichment procedures (using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes) were then used to identify functional groups of mRNA. Results At 10 to 12 weeks, brains showed neuronal migration to be upregulated. From 10 to 18 weeks, brains showed genes coding for neuronal migration, differentiation and connectivity upregulated. ALDH1A1 and NPY genes, marker of spinal cord and striatum, were upregulated in B1 and B3 brains, respectively. Also, SLITRK6‐HAS2 and CRYAB‐PCDH18 genes for ear and eye sensory input were upregulated in B1. Conclusions For the first time, brain global gene expression was described in human samples. Period B1 was dominated by genes coding for neuronal migration, differentiation, programmed cell death and sensory organs. B3 was dominated by neuronal proliferation, branching and myelination. Creating such a database will allow comparison with abnormals in future studies. © 2014 John Wiley & Sons, Ltd.